2018
DOI: 10.1177/2050640617717156
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age at diagnosis on disease progression in patients with primary sclerosing cholangitis

Abstract: Background: The median age of diagnosis of primary sclerosing cholangitis (PSC) is $30-40 years. Objective: We aimed to analyse disease progression and liver-dependent survival in patients diagnosed with PSC after 50 years of age. Methods: Patients with PSC were analysed with regard to their age at diagnosis. Patients with a first diagnosis of PSC after the age of 50 years were considered as the late-onset group. Results: A total of 32/215 (14.9%) patients were diagnosed with PSC after 50 years of age. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
3
16
1
Order By: Relevance
“…We found that younger patients had significantly higher IgG levels and were a group that is at risk of shortened survival for this reason. In contrast to our findings, it has been previously reported that late-onset PSC and increased age in general are associated with poor survival promoted by the increased CCA risk over time [2426]. However, our data underlines the fact that close surveillance is important in young patients with elevated IgG levels.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that younger patients had significantly higher IgG levels and were a group that is at risk of shortened survival for this reason. In contrast to our findings, it has been previously reported that late-onset PSC and increased age in general are associated with poor survival promoted by the increased CCA risk over time [2426]. However, our data underlines the fact that close surveillance is important in young patients with elevated IgG levels.…”
Section: Discussioncontrasting
confidence: 99%
“…PSC affects all age groups, with older age at diagnosis reportedly associated with worse transplant-free survival. 1,6,8 However, causal mortality analysis according to age at PSC diagnosis has not been determined. Such findings have critical implications for interventional trial design, as 40 to 50% of all deaths may not be attributable to liver disease.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 Phenotypic diversity according to sex and age may also influence the clinical course that patients experience. 8,11 Whilst the majority of datasets derive from Caucasian populations, a recent study indicates that PSC may be as common in patients of Afro-Caribbean descent. 12 However, it is unknown whether heritage-specific differences in disease risk exist in PSC.…”
Section: Methodsmentioning
confidence: 99%
“…PSC is typically diagnosed in the third through fifth decades of life and has an approximately 3 to 1 male to female predilection. Diagnosis of PSC after the age of 50 is considered late onset and one study showed that late onset PSC was associated with more frequent dilatation therapy, recurrent cholangitis, and decreased transplant-free survival when compared to those diagnosed with PSC before age 50 [25]. PSC is a relatively rare disease and while the incidence is not well established, a systematic review of 8 studies from North America and Europe in 2011 showed an overall incidence of 0.77 per 100,000 person years [26].…”
Section: Introductionmentioning
confidence: 99%